Case Report: Myoclonic and tremulous movements associated with COQ8A-related coenzyme Q10 deficiency type 4 - Wang, Di; Zhang, Guojian; Fang, Xiaojing; Liu, Fang; Wang, Li (Frontiers in Genetics, 2026)
BackgroundPrimary coenzyme Q10 (CoQ10) deficiency is a rare, treatable mitochondrial disorder often caused by biallelic pathogenic variants in COQ8A gene (also known as ADCK3). It typically manifests as childhood-onset cerebellar ataxia with variable multisystem involvement. Early recognition is critical, as CoQ10 supplementation has potential to significantly alleviate clinical manifestations and modify natural progression of the disease. Here, we provide a rare phenotype of paroxysmal dyskinesias caused by compound heterozygous variants of COQ8A gene.CaseA 21-year-old man presented with myoclonic tremor, mild dysarthria, ataxia and emotional instability. The brain MRI showed cerebellar atrophy. Biochemical workup revealed low plasma CoQ10 levels. Whole-exome sequencing identified compound heterozygous COQ8A variants: two novel missense substitutions [NM_020247.5:c.641T>A (p.Leu214Gln), NM_020247.5:c.1621T>C (p.Ser541Pro)], each inherited from an asymptomatic parent. The patient was initiated on oral CoQ10 at a dose of 200 mg twice daily, accompanied by supportive interventions targeting emotional regulation. A marked improvement in tremor symptoms was observed shortly after treatment initiation; however, intermittent muscle tremors persisted during periods of emotional agitation. At 1-year follow-up, the patient remained on CoQ10 at 300 mg twice daily and levetiracetam at 500 mg twice daily, with sustained symptom control.ConclusionThis case highlights that COQ8A-related CoQ10 deficiency can present with serious neurological crises among young people and underscores the importance of rapid genetic diagnosis in such scenarios. Early and aggressive CoQ10 supplementation led to clinical stabilization in our patient, reinforcing that primary CoQ10 deficiency is a reversible cause of neurodegenerative disease. We emphasize genotype-phenotype diversity in COQ8A disease and the crucial need for early detection and treatment to improve prognosis. We propose that clinicians maintain a high index of suspicion for primary CoQ10 deficiency in patients presenting with unexplained dystonia or ataxia, as timely intervention may significantly improve clinical outcomes.